2013
DOI: 10.1021/ci400202t
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Inhibitors of Mycobacterium tuberculosis InhA Enzyme Using Virtual Screening and a 3D-Pharmacophore-Based Approach

Abstract: Mycobacterium tuberculosis InhA (MtInhA) is an attractive enzyme to drug discovery efforts due to its validation as an effective biological target for tuberculosis therapy. In this work, two different virtual-ligand-screening approaches were applied in order to identify new InhA inhibitors' candidates from a library of ligands selected from the ZINC database. First, a 3-D pharmacophore model was built based on 36 available MtInhA crystal structures. By combining structure-based and ligand-based information, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 45 publications
3
59
0
3
Order By: Relevance
“…These mycolic acids have been associated with M. tuberculosis virulence [9], the ability of M. tuberculosis to survive and replicate inside M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 interactions involving a ribose hydroxyl, the Tyr158 hydroxyl and a hydrogen bond acceptor in the compounds. Consistent with our strategy [22], this substrate-proteinligand interaction has been observed as a pharmacophoric point in virtual screening campaigns for novel MtInhA inhibitors. However, the structural and electronic requirements for these hydrogen bond donor-acceptor pairs have not been extensively examined.…”
Section: Introductionsupporting
confidence: 77%
“…These mycolic acids have been associated with M. tuberculosis virulence [9], the ability of M. tuberculosis to survive and replicate inside M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 interactions involving a ribose hydroxyl, the Tyr158 hydroxyl and a hydrogen bond acceptor in the compounds. Consistent with our strategy [22], this substrate-proteinligand interaction has been observed as a pharmacophoric point in virtual screening campaigns for novel MtInhA inhibitors. However, the structural and electronic requirements for these hydrogen bond donor-acceptor pairs have not been extensively examined.…”
Section: Introductionsupporting
confidence: 77%
“…In a recent study, a series of novel InhA inhibitors was identified through a virtual screening strategy. The authors employed a multistage approach, integrating pharmacophore modeling and molecular docking [207]. First, a four-point 3D pharmacophore model was generated by superimposing 36 InhA crystallographic structures available in the PDB.…”
Section: Discovery Of Mycobacterium Tuberculosis Inha Inhibitors Usinmentioning
confidence: 99%
“…Two different virtual-screening approaches were applied in order to identify novel inhibitors for the Mycobacterium tuberculosis InhA (MtInhA) target [73]. First, a 3-D pharmacophore model was built based on 36 available MtInhA crystal structures.…”
Section: Case Studymentioning
confidence: 99%